Improving transversal competences by using wikis in collaborative work - Marta Guinau; Elisabet Playà; Meritxell Aulinas; Laura Rosell; Lluís Rivero (OmniaScience, 2017)
Work on transversal competences in university degrees is a teaching line entirely established since the implementation of the European Credit Transfer System (ECTS). Nevertheless, undergraduate students present shortcomings in the development of some of these competences, especially on collaborative work, time management, oral and writing expression, and on the use of information resources. This paper presents a virtual tool and associated guidelines to enhance the information management during the development of collaborative works, and to facilitate the information availability among the students. Moreover, this tool and the guideline improve the individual monitoring and evaluation of the contributions of the students to the work. The proposal presented in this work belongs to a teaching innovation project carried out in the Earth Sciences Faculty of the Universitat de Barcelona, and implemented in the subjects General Geology (first-year in the Engineering Geology degree, 6 ECTS) and Geochemistry (third-year course in the Geology degree, 9 ECTS).